The Impact of The Indexs Card Match (ICM) Matching Strategy on The Learning Outcomes of Aqidah For the Second Year Students at Darussalam Gontor For Girls 1 on 2020-2021 - Ihwan Mahmudi; Sintiya Rizqi Nur Ardiani (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Education is a conscious and planned effort to realize the learning atmosphere and learning process of learners actively develop their potential to have religious spiritual power, self-control, personality, noble moral intelligence and skills required in themselves, society, nation and country. With education, people will have more high human resources. Like a human being who is equipped with reason and mind to think. In the teaching and learning process, researchers found problems contained in the learning outcomes of students with material Science 'Aqaid class 2 KMI in Modern of Islamic Boarding School Darussalam Gontor for Girls 1st Campus that is with the decrease in the value of the second half of the 2019/2020 school year. Which is the second semester of grade 2 of the 2019/2020 school year which is 4.07 while for the graduation standard is 4.90. Because there is a decrease in student learning outcomes by applying appropriate strategies in the learning of 'Aqaid materials so as to help students in improving learning outcomes in the material 'Aqaid Grade 2 at Modern of Islamic Boarding School Darussalam Gontor for Girls 1st Campus. With Index Card Match (ICM) learning strategy that is in accordance with the objectives to be achieved in learning that covers the realm of knowledge by remembering, understanding, and analyzing. In this study, researchers used true experimental design as a method used for observations conducted by manipulating research objects as well as the existence of control classes and experimental classes. Data collection techniques of student learning results using tests with instruments in the form of posttest only. Analysis of the results of the study using non-parametric statistics in the form of Mann-Whitney tests. Based on the results of this study, there is an influence of Index Card Match (ICM) learning strategy on the results of learning 'aqaid from Mann-Whitney test with Sig value. (2-tailed) is: 0,000 < 0,05. From the results of this study, the difference in the value of learning outcomes between the control class and the experimental class was 5,56%.